2016
DOI: 10.1051/0004-6361/201526999
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of scattering at 8 μm: Brighter than you think

Abstract: Context. Extinction and emission of dust models need for observational constraints to be validated. The coreshine phenomenon has already shown the importance of scattering in the 3 to 5 µm range and its ability to validate dust properties for dense cores. Aims. We want to investigate whether scattering can also play a role at longer wavelengths and to place even tighter constraints on the dust properties. Methods. We analyze the inversion of the Spitzer 8 µm map of the dense molecular cloud L183, to examine th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…In molecular clouds and dense cold cores, the observed decrease in the mid-IR to far-IR emission ratio (Stepnik et al 2003;Flagey et al 2009), the increase in the dust far-IR/millimeter opacity and spectral index (Martin et al 2012;Bracco et al 2017), and the increased scattering efficiency from the near-to mid-IR (Pagani et al 2010) point out to an evolution of dust properties in dense regions. It was suggested that these observations could be explained if dense structures contain aliphatic-rich ice-mantled grains (Jones et al 2013;Ysard et al 2016), or already evolved micrometer-sized grains (Steinacker et al 2010;Lefèvre et al 2016). A rather unexplored step on the evolutionary sequence lead-ing to the formation of planets is the protostellar stage, and even more so the main accretion phase (Class 0 protostars, André et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In molecular clouds and dense cold cores, the observed decrease in the mid-IR to far-IR emission ratio (Stepnik et al 2003;Flagey et al 2009), the increase in the dust far-IR/millimeter opacity and spectral index (Martin et al 2012;Bracco et al 2017), and the increased scattering efficiency from the near-to mid-IR (Pagani et al 2010) point out to an evolution of dust properties in dense regions. It was suggested that these observations could be explained if dense structures contain aliphatic-rich ice-mantled grains (Jones et al 2013;Ysard et al 2016), or already evolved micrometer-sized grains (Steinacker et al 2010;Lefèvre et al 2016). A rather unexplored step on the evolutionary sequence lead-ing to the formation of planets is the protostellar stage, and even more so the main accretion phase (Class 0 protostars, André et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…2.2). While we have already found a reasonable solution to model L183 in the NIR and MIR [6], the NIKA2 data will help to derive the best grain composition thanks to SIGMA and 3D radiative transfer modeling. Figure 2.…”
Section: Constraints Obtained From Other Wavelengthsmentioning
confidence: 84%
“…The first step of our approach is to build a 3D density model of the cloud independently from scattered light or degenerated emission process. Our density model relies on dust extinction as measured by reddening in the NIR, and the PSC densities are deduced from molecular observations of N 2 H + and N 2 D + [6,13], assuming thermalized gas and dust and rotational symmetry 1 (see Fig. 1).…”
Section: Constraints Obtained From Other Wavelengthsmentioning
confidence: 99%
See 2 more Smart Citations